2021
DOI: 10.1016/j.infpip.2021.100163
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated infections and antimicrobial use in surgical wards of a large urban central hospital in Blantyre, Malawi: a point prevalence survey

Abstract: Summary Background There are limited data on healthcare-associated infections (HAI) from African countries like Malawi. Aim We undertook a point prevalence survey of HAI and antimicrobial use in the surgery department of Queen Elizabeth Central Hospital (QECH) in Malawi and ascertained the associated risk factors for HAI. Methods A cross-sectional point prevalence survey (PPS) was carried out in the surgery department of QECH. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…This systematic review and meta-analysis included a total of 43 studies conducted on 798 712 patients (ranging from 105 24 to 633 990 25 study participants). Among the included studies, 5 were conducted in China, 25 - 29 3 in Ethiopia, 30 - 32 3 in the USA, 33 - 35 2 in Switzerland, 36 , 37 2 in Benin, 38 , 39 2 in Germany, 40 , 41 2 in Italy, 42 , 43 2 in Iran, 44 , 45 and 2 in Poland.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review and meta-analysis included a total of 43 studies conducted on 798 712 patients (ranging from 105 24 to 633 990 25 study participants). Among the included studies, 5 were conducted in China, 25 - 29 3 in Ethiopia, 30 - 32 3 in the USA, 33 - 35 2 in Switzerland, 36 , 37 2 in Benin, 38 , 39 2 in Germany, 40 , 41 2 in Italy, 42 , 43 2 in Iran, 44 , 45 and 2 in Poland.…”
Section: Resultsmentioning
confidence: 99%
“…One in each of France, 48 Turkey, 49 Cuba, 50 Thailand, 51 Albania, 52 Malawi, 24 Saudi Arabia, 53 Ghana, 54 Nigeria, 55 Argentina, 56 Rwanda, 57 Tanzania, 58 Georgia, 59 South Africa, 60 Tunisia, 61 Nepal, 62 Herzegovina, 63 Australia, 64 India, 65 and Cameroon. 66 Among the included studies, the highest incidence of SSI was reported in Tanzania, 58 which accounted for 26.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies were included in the qualitative summary of the prevalence of HAIs among hospitalized patients in Africa. Overall, the prevalence of HAIs ranged between 7.24% and 28% [4,[19][20][21][22][23][24][25][26][27][28][29][30][31][32], and the prevalence varied between the regions in Africa. (2.0-10.8%) [22,26,28,30,31].…”
Section: Prevalence and Distribution Of Hais Among Hospitalized Patie...mentioning
confidence: 99%
“…This systematic review and meta-analysis included a total of 38 studies conducted on 981,221 patients (ranging from 105 31 to 633 990 32 study participants). Among the included studies, 7 were conducted in China, 32 - 38 2 in each Switzerland, 39 , 40 USA, 41 , 42 Turkey, 43 , 44 Iran, 45 , 46 Italy, 47 , 48 and Poland.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 7 were conducted in China, 32 - 38 2 in each Switzerland, 39 , 40 USA, 41 , 42 Turkey, 43 , 44 Iran, 45 , 46 Italy, 47 , 48 and Poland. 49 , 50 However, one articles were selected from each Benin, 51 France, 52 Cuba, 53 Thailand, 54 Albania, 55 Malawi, 31 Saudi Arabia, 56 Ghana, 57 Argentina, 58 Ethiopia, 59 Tunisia, 60 Belgium, 61 Nepal, 62 Kuwait, 63 Germany, 64 Australia, 65 Herzegovina, 66 India, 67 Cameroon 68 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%